2017
DOI: 10.1242/jcs.197285
|View full text |Cite
|
Sign up to set email alerts
|

Defective signaling, osteoblastogenesis and bone remodeling in a mouse model of connexin 43 C-terminal truncation

Abstract: In skeletal tissue, loss or mutation of the gap junction protein connexin 43 (Cx43, also known as GJA1) in cells of the osteoblast lineage leads to a profound cortical bone phenotype and defective tissue remodeling. There is mounting evidence in bone cells that the C-terminus (CT) of Cx43 is a docking platform for signaling effectors and is required for efficient downstream signaling. Here, we examined this function, using a mouse model of Cx43 CT-truncation (Gja1 K258Stop). Relative to Gja1 +/− controls, male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 60 publications
3
61
1
2
Order By: Relevance
“…Similarly, the altered bone material mechanical properties, with decreased stiffness, of mice lacking osteocytic Cx43 are reversed by the truncated Cx43. Nevertheless, our in vitro data, together with our previous in vivo study (Pacheco‐Costa et al ., 2015) and a recent report in male mice expressing only the truncated Cx43 (Moorer et al ., 2017), suggest that the trans‐membrane and cytoplasmic amino‐terminal domains are sufficient to maintain osteocyte viability and preserve normal cortical bone geometry and material properties. Future studies using mice overexpressing Cx43 in osteocytes (currently under development in our laboratory) will allow us to determine whether maintenance of Cx43 levels reverses the increased osteocyte apoptosis and, at least partially, the skeletal phenotype of old mice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the altered bone material mechanical properties, with decreased stiffness, of mice lacking osteocytic Cx43 are reversed by the truncated Cx43. Nevertheless, our in vitro data, together with our previous in vivo study (Pacheco‐Costa et al ., 2015) and a recent report in male mice expressing only the truncated Cx43 (Moorer et al ., 2017), suggest that the trans‐membrane and cytoplasmic amino‐terminal domains are sufficient to maintain osteocyte viability and preserve normal cortical bone geometry and material properties. Future studies using mice overexpressing Cx43 in osteocytes (currently under development in our laboratory) will allow us to determine whether maintenance of Cx43 levels reverses the increased osteocyte apoptosis and, at least partially, the skeletal phenotype of old mice.…”
Section: Discussionmentioning
confidence: 99%
“…Runx2, an important transcription factor necessary for osteoblast differentiation and bone formation, controls expression of the Bglap and osteopontin genes [50, 51]. Numerous in vitro and in vivo studies have shown that early osteogenic differentiation at the level of Runx2 is among the primary mechanisms by which Cx43 exerts its action on bone cells [52-57]. Our results are consistent with a previous report showing inhibition of Cx43 decreases the expression of Runx2 during differentiation of hBMSC into osteoblasts [53].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of GSK-3beta can be inhibited by phosphorylation at Ser-9 [61]. Furthermore, the impact of Cx43 on beta-catenin activity and GSK are also well established [56, 57, 62], whereas the mechanism by which the defects in Cx43 cause skeletal development deficiency has not been shown [17]. Our research involves the roles of Cx43 in skeletal development.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting of whole-cell extracts isolated from cells in culture after FSS or extracts isolated from murine long bone was done as previously described (68, 70). Equal amounts of protein were loaded and electrophoresed on 10% SDS–polyacrylamide gel electrophoresis gels and transferred to polyvinylidene difluoride membranes.…”
Section: Methodsmentioning
confidence: 99%